1991
DOI: 10.1007/bf02660610
|View full text |Cite
|
Sign up to set email alerts
|

Studies on glycolipids of kenaf, english walnut, myrobalan and manila tamarind seeds of the Vidarbha region (India)

Abstract: Studies on the glycolipid compositions of Kenaf, English walnut, Myrobalan and Manila tamarind seeds found in the Vidarbha region of Central India have been carded out by silicic acid column chromatography and thin-layer chromatography (TLC). The total glycolipids have been separated into individual components such as monogala~ tosyldiglycerides 20-28%, digalactosyldiglycerides 40-41%, sterylgalactosides 15-18%, acylated sterylgalactosides 8-15% and unidentified components 0.8-2%. The fatty acid composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many studies have reported that lipase activity increased as the chain length of triglycerides became shorter, and it appears to be activated differently depending upon the type of oil 2,19,47,48 . Walnut oil is mainly composed of triglycerides, but also contains glycolipids such as digalactosyl diglycerides (DGDG) and monogalactosyl diglycerides (MGDG) 49 . DGDG inhibits lipolysis as it tends to resist displacement by bile salts at the oil–water interface 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that lipase activity increased as the chain length of triglycerides became shorter, and it appears to be activated differently depending upon the type of oil 2,19,47,48 . Walnut oil is mainly composed of triglycerides, but also contains glycolipids such as digalactosyl diglycerides (DGDG) and monogalactosyl diglycerides (MGDG) 49 . DGDG inhibits lipolysis as it tends to resist displacement by bile salts at the oil–water interface 50 .…”
Section: Resultsmentioning
confidence: 99%
“…2,19,47,48 Walnut oil is mainly composed of triglycerides, but also contains glycolipids such as digalactosyl diglycerides (DGDG) and monogalactosyl diglycerides (MGDG). 49 DGDG inhibits lipolysis as it tends to resist displacement by bile salts at the oil-water interface. 50 Chu et al reported that when an emulsion containing DGDG and lecithin was decomposed by lipase in the presence of bile acid, the total amount of FFA released was increased compared to an emulsion prepared with DGDG alone.…”
Section: Ionic Strengthmentioning
confidence: 99%